Correspondence from Representatives re: BHP Billiton Liquefied Natural Gas (LNG) - Various
Correspondence from various representatives re: the U.S. Environmental Protection Agency's (EPA) handling of the application for the BHP Billiton liquefied natural gas (LNG) floating storage and regasification project off the coast of Ventura County, California.